Keberlanjutan, Intensitas Modal, dan Manajemen Pajak dengan Moderasi Ukuran Perusahaan: Studi pada Emiten IDX Food & Beverage Tahun 2020 - 2024 - Eka Putri Julianti Wibowo (Pajak dan Manajemen Keuangan, 2026)
The purpose of this study is to examine the effect of sustainability and capital intensity on tax management, with company size as a moderating variable, using a quantitative research method. Secondary data from financial statements and annual reports were used, employing purposive sampling techniques, resulting in 28 issuers with a total of 140 observation data samples that met the research criteria. Data processing included descriptive statistical analysis, classical assumption tests, multiple linear regression analysis with moderated regression analysis (MRA), and hypothesis testing, including t and F statistical tests. The results are: (1) sustainability has a positive and significant effect of 0.0008 ≥ 0.05 on tax management; (2) capital intensity has a negative and insignificant effect of 0.676 ≥ 0.05 on tax management; (3) company size can moderate and strengthen the effect of sustainability on tax management, with a significance of 0.0003 ≤ 0.05.(4) company size is unable to moderate the effect of capital intensity on tax management, with a significance of 0.984 ≥ 0.05; (5) sustainability and capital intensity simultaneously affect tax management with 0.0002 ≤ 0.05.